Inclusive search for a highly boosted higgs boson decaying to a bottom quark-antiquark pair - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2018)
An inclusive search for the standard model Higgs boson (H) produced with large transverse momentum (pT) and decaying to a bottom quark-antiquark pair (bb) is performed using a data set of pp collisions at s=13 TeV collected with the CMS experiment at the LHC. The data sample corresponds to an integrated luminosity of 35.9 fb-1. A highly Lorentz-boosted Higgs boson decaying to bb is reconstructed as a single, large radius jet, and it is identified using jet substructure and dedicated b tagging techniques. The method is validated with Z→bb decays. The Z→bb process is observed for the first time in the single-jet topology with a local significance of 5.1 standard deviations (5.8 expected). For a Higgs boson mass of 125 GeV, an excess of events above the expected background is observed (expected) with a local significance of 1.5 (0.7) standard deviations. The measured cross section times branching fraction for production via gluon fusion of H→bb with reconstructed pT>450 GeV and in the pseudorapidity range -2.5<η<2.5 is 74±48(stat)-10+17(syst) fb, which is consistent within uncertainties with the standard model prediction.